Study on the Influence Mechanism of Science and Technology Finance on the Technological Innovation of High-tech Industry - Li, Sui; Shi, Guangye (International Journal of Global Economics and Management, 2025)
High-tech industries are leaders in technological innovation. Their high innovativeness, high investment, and high risk make the contradiction between capital supply and demand a key factor constraining industrial development. Science and technology finance is an open system composed of various financial entities and institutional environments. As a crucial guarantee for technological innovation and a critical link in enhancing financial services to the real economy, it will provide the strongest support for the development of high-tech industries. This paper delves into the direct impact mechanisms of science and technology finance on technological innovation in high-tech industries from five aspects: government, banks, venture capital, capital markets, and technology insurance. It also discusses the indirect impact mechanisms of science and technology finance on technological innovation in high-tech industries from two perspectives: competitive effects and spatial spillover effects. Finally, it proposes policy recommendations aimed at promoting technological innovation and the development of science and technology finance in high-tech industries across regions, improving the science and technology finance system, strengthening the role of science and technology finance, focusing on spillover effects between different regions, and facilitating the free flow of resources.